Penerapan Single Page Application pada Sistem KRS Online UMS - Ristyabudi, Aryani, Husni Thamrin, S.T., M.T., Ph.D (2016)
Universitas Muhammadiyah Surakarta (UMS) has established web-based application for student study plan (or Kartu Rencana Studi - KRS online) for several years. This paper describes a study to consider applying an emerging concept of Single Page Application (SPA) into the application. SPA is a new breakthrough that provides only a single page web page for various activities. In the KRS online system, we tried to implement latest web technologies such as HTML5 and AngularJS. Performance testing was conducted using Wireshark to measure the number of transferred data and the total of time required for accessing the system. From test results, it can be concluded that the system with SPA uses less than one tenth of the original number of data transferred during the system access. Moreover, the system with SPA saves the total of time that are required for accessing the KRS online system to as low as one third of the original system.